INFLUENCE OF PROFITABILITY, ASSET STRUCTURE, SALES GROWTH AND BUSINESS RISK ON INVESTMENT - Dedi Dedi; Seyla Seyla; Wirda Lilia (Jurnal Ipteks Terapan (Research Of Applied Science And Education ), 2022)
This study aims to determine the effect of profitability, asset structure, sales growth and business risk on investment. In the food and beverage industry companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019 the data used comes from the Indonesian stock exchange through the www.idx.co.id site and has been selected based on the criteria in this study. The population used in this study is companies engaged in the food and beverage industry, totaling 26 companies, using a purposive sample, the samples obtained are 14 companies. With this research, it becomes a science to help further researchers and also students or the general public who need information. From this research, it can be seen that profitability has a partial effect on the amount of investment. Asset structure, sales growth, and business risk are not partially affected and have no significant impact on investment in the food and beverage industry. But all variables affect simultaneously. The choice of this sector is due to the fact that currently Indonesia is the country with the 4th most populous population and is a consumption country. Of course, the need for food and beverages will always increase so that many companies are built on that basis, which made me interested in researching it.